In vitro analyses of paracrine effects of murine classically activated macrophage on beige adipocyte metabolism - Jingfei Yao; Dongmei Wu; Yifu Qiu (STAR Protocols, 2022)
Summary: The communication between macrophage and adipocyte plays a critical role in the initiation and development of metabolic inflammation, which is difficult to study in vivo. Here, we provide a step-by-step protocol using differentiated cells to investigate the paracrine effects of classically activated macrophage on beige adipocyte metabolism in vitro. This protocol uses bone-marrow-derived macrophage and SVF-derived UCP1+ beige adipocyte in a culture model to study immune regulation of adipocyte metabolism by western blot analyses.For complete details on the use and execution of this protocol, please refer to Yao et al. (2021). : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.